An iminodiacetate-modified conjugated polyelectrolyte for fluorescent labeling of histidine-tagged proteins. Issue 30 (6th March 2017) - Cai, Kai; Tan, Ying; Tan, Chunyan; Wu, Jiatao; Wu, Pan; Liang, Jiamei; Liu, Shuwen; Zhang, Bibo; Jiang, Yuyang
Abstract : An iminodiacetate-modified conjugated polyelectrolyte was used in the fluorescent labeling of hexahistidine-tagged proteins. Abstract : The iminodiacetate–Ni 2+ –hexahistidine system is extensively used in protein purification. In this study, an anionic conjugated polyelectrolyte (CPE) with a poly( p -phenylene ethynylene) backbone and iminodiacetate side chains, named PPEIDA, was designed and synthesized. Recognition and visualization of hexahistidine-tagged (His-tagged) proteins using PPEIDA was demonstrated.